The Future of the Past in Latin America - Peters, Stefan (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The article discusses the recent developments in memory studies at the beginning of the 20th century and the recent dynamics in memory politics and in the memory culture of Latin America. Based on this analysis, the article arguing in favor of repeating memory studies, placing special emphasis on three points that can guide the future of memory studies in Latin America: memories and inequalities, the study of (non) memory in its two edges of oblivion and silence, as well as the transregional dynamics of memory. The article closes with some reflections on the importance of memory and the specifics of the success of a memory policy. In this part, the article argues that the field of memory will always be controversial and that only these disputes can change memory to stay alive.